Acute effects of prolonged intermittent low-intensity isometric warm-up schemes on jump, sprint, and agility performance in collegiate soccer players - Pojskic, H.; Pagaduan, J. C.; Babajic, F.; Uzicanin, E.; Muratovic, M.; Tomljanovic, M. (Biology of Sport, 2015)
The aim of the present study was to compare the effects of different warm-up interventions on jump, sprint and agility performance in collegiate soccer players. Twenty-one healthy male college soccer players (age: 20.14 ± 1.65 years; body height: 179.9 ± 8.34 cm; body mass: 74.4 ± 13.0 kg; % body fat: 9.45 ± 4.8) participated in the study. Subjects underwent four different randomized warm-up protocols separated by at least 48 hours. The warm-up schemes were: 1. no conditioning contraction protocol (NCC); 2. dynamic stretching (DS); 3. prolonged intermittent low-intensity isometric exercise (ST); and, 4. ST with an additional external load equal to 30% of body weight (ST + 30% BW). All interventions were preceded by a general warm-up. Results from one-way repeated measures ANOVA demonstrated a significant difference in countermovement jump (CMJ).